Agro Inovasi Berbasis Infus : Efisiensi Keuangan dan Peningkatan Produktivitas Tanaman Cabai di Lahan Pertanian Desa - Rifa’i, Akhmad; Chintya Putri Prasetyaningayu; Putri Ayu Umahatul Permatasari; Mayasita Lailatul Fitria; Salma Fatia; Akbar Khairat Ajiseno; Imam Aditya; Yesy Amhelya; Alfan Nawal Aufa; Muhammad Farkhan Ashari; Firlia Sayidatu Zahrok; Chandra Febrian Amukti; Furqan Hudana Tsabit; Fenti Zya Ain Salwa Q; M.Aditya Rahmad G; Alya Fitriani; Muhammad Putra Pratama; Inas Maki Jannata Khulud (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2026)
Agriculture is a vital sector in Gunung Gede Village, Wonotirto District, Blitar Regency, but faces labor constraints due to the migration of productive age groups and water availability constraints due to the hilly geographical conditions. The traditional irrigation system still in use tends to be wasteful of energy and water, resulting in low efficiency in horticultural plant care. This study aims to develop and implement an infusion-based irrigation innovation as a simple, inexpensive, and environmentally friendly solution to improve water and labor efficiency. The method used is a participatory approach through the Community Service (PkM) program, including land surveys, consultations with farmer groups, tool design, outreach, and direct field practice. The implementation results show that the infusion system can save water use by 30–40%, reduce dependence on labor, and improve the consistency of water and nutrient delivery to plants. In addition, this innovation increases farmer enthusiasm and has the potential to attract the younger generation to become involved in the agricultural sector. In conclusion, infusion-based agro-innovation is effective as an adaptive solution to support water-efficient agriculture in hilly areas and has the potential to be developed sustainably.